Accuracy of Provider-Selected Indications for Antibiotic Orders. (18th January 2018) - Heil, Emily L.; Pineles, Lisa; Mathur, Poonam; Morgan, Daniel J.; Harris, Anthony D.; Srinivasan, Arjun; Thom, Kerri A.
Abstract : Documentation of antibiotic indication provides helpful information for antimicrobial stewardship, but accuracy is not understood. Review of 396 antibiotic orders in a pediatric ICU and adult medicine step-down unit found 90% agreement between provider-selected indication and independent review. Prompts to enter antibiotic indication during order entry provide largely accurate information. Infect Control Hosp Epidemiol 2018;39:111–113